Interfollicular epidermal stem-like cells for the recreation of the hair follicle epithelial compartment - Abreu, Carla M. (2021)
Background Hair follicle (HF) development and growth are dependent on epithelial-mesenchymal interactions (EMIs). Dermal papilla (DP) cells are recognized as the key inductive mesenchymal player, but the ideal source of receptive keratinocytes for human HF regeneration is yet to be defined. We herein investigated whether human interfollicular epidermal keratinocytes with stem-like features (EpSlKCs), characterized by a Î±6bri/CD71dimexpression, can replace human hair follicular keratinocytes (HHFKCs) for the recreation of the HF epithelium and respective EMIs. Methods The Î±6bri/CD71dimÂ cellular fraction was selected from the whole interfollicular keratinocyte population through fluorescence-activated cell sorting and directly compared with follicular keratinocytes in terms of their proliferative capacity and phenotype. The crosstalk with DP cells was studied in an indirect co-culture system, and EpSlKC hair forming capacity tested in a hair reconstitution assay when combined with DP cells. Results EpSlKCs exhibited a phenotypic profile similar to follicular keratinocytes and were capable of increasing DP cell proliferation and, for short co-culture times, the number of alkaline phosphatase-active cells, suggesting an improvement of their inductivity. Moreover, the recreation of immature HFs and sebaceous glands was observed after EpSlKC and DP cell co-grafting in nude mice. Conclusions Our results suggest that EpSlKCs are akin to follicular keratinocytes and can crosstalk with DP cells, contributing to HF morphogenesis in vivo, thus representing an attractive epithelial cell source for hair regeneration strategies.